Chuva de sementes em Florestas Estacional Semidecidual Submontana, Espirito Santo - Santos, Jaqueline Pêgo Quintino (2017)
In tropical forest ecosystems, studies about ecological aspects are essential for conservation. Among these ecological mechanisms, stands out the importance of seed rain, which is a key component for understand the dynamics of forest populations. In this context, the present study aimed to characterize the seed rain of a fragment, correlating the seed deposition dynamics with the climatic seasonality, floristic, regeneration and ecological attributes of the species, such as: sexual system, pollination syndrome and dispersion and type of fruit. The research was carried out in a fragment of Submontane Semidecidual Seasonal Forest, in the Private Reserve of Natural Patrimony (RPPN) Cafundó, which belongs Cachoeiro de Itapemirim, Espírito Santo. The seed rain collections occurred in 12 fixed plots during April / 2013 to March / 2016.The three years together totaled 28,482 propagules, belonging to 102 morphospecies and 28 botanical families. It was verified variation in the richness and the intra-annual and interannual abundance of the seed rain in the RPPN-Cafundó. Seed rainfall was highest in the dry period, mainly composed of anemocoric species and was also high at the end of the rainy season, which the zoocoric species were more abundant. The similarity between floristic and seed rain was low, showing that the species of this mechanism can be from other areas. As for the sexual systems of the species registered in the seed rain, these followed the suggested pattern for tropical forests, with 71% hermaphrodite, 16% dioecious and 13% monoic species. The data found throughout the study contribute to understanding how to maintain the biodiversity of a forest environment.